PEMBUATAN BAHAN AJAR FISIKA BERBASIS VIDEO MENGGUNAKAN SPARKOL VIDEOSCRIBE UNTUK PEMBELAJARAN FISIKA SISWA KELAS X SMA - Siti Fajar Aldilha Yudha; Asrul Asrul; Zulhendri Kamus (Universitas Negeri Padang, 2016)
Physics subject in learning need to be supported with learning materials to help students understanding the physics concept. Currently, the use of teaching materials using IT to support physics learning is limited. Alternative solution of this problem is a video-based physics learning materials using sparkol videoscribe. This study aims to produce product such as video-based physics learning materials on the subject matter of geometry optics and optical instruments that valid and practical.Types of this research is research and development (R&D). This method consists of 10 steps according to Sugiyono (2012:409), that are the potential and problems, data collection, product design, design validation, design revisions, product testing, product revision, user testing, product revision, and mass production. However, the study was only conducted until the seventh step. The object of research is a video-based physics learning materials using sparkol videoscribe that validated by 5 validator, and 3 teachers and 10 students to practicalities. Data were analyzed with descriptive analysis techniques.Based on research that has been done, product of video-based physics learning materials using sparkol videoscribe is categorized valid from the aspects of material substance, appearance visual communication, instructional design, and the use of software with an average value of 87.55%. Product research is also considered practical by teachers from the content aspect of teaching materials, ease of use, efficiency of learning time, and benefits with an average value of 84.83% and practical as well as categorized by students with an average value of 87,08%